Exfoliation of a non-van der Waals material from iron ore hematite - Puthirath Balan, Aravind; Radhakrishnan, Sruthi; Woellner, Cristiano F; Sinha, Shyam K; Deng, Liangzi; Reyes, Carlos de Los; Rao, Banki Manmadha; Paulose, Maggie; Neupane, Ram; Apte, Amey; Kochat, Vidya; Vajtai, Robert; et al. (Nature nanotechnology, 2018)
With the advent of graphene, the most studied of all two-dimensional materials, many inorganic analogues have been synthesized and are being exploited for novel applications. Several approaches have been used to obtain large-grain, high-quality materials. Naturally occurring ores, for example, are the best precursors for obtaining highly ordered and large-grain atomic layers by exfoliation. Here, we demonstrate a new two-dimensional material 'hematene' obtained from natural iron ore hematite (α-Fe O ), which is isolated by means of liquid exfoliation. The two-dimensional morphology of hematene is confirmed by transmission electron microscopy. Magnetic measurements together with density functional theory calculations confirm the ferromagnetic order in hematene while its parent form exhibits antiferromagnetic order. When loaded on titania nanotube arrays, hematene exhibits enhanced visible light photocatalytic activity. Our study indicates that photogenerated electrons can be transferred from hematene to titania despite a band alignment unfavourable for charge transfer.